42.6: Maxwellian‐viewing‐super‐multi‐view near eye display using a Pancharatnam‐Berry optical element. (26th August 2021) - Wang, Lin; Li, Yan; Liu, Shuxin; Li, Xiang; Su, Yikai
Abstract : In order to overcome the accommodation and convergence conflict and enlarge depth of field (DOF) in AR displays, a Maxwellian‐viewing‐super‐multi‐view (MV‐SMV) display system is proposed. The system employs a Pancharatnam‐Berry optical element (PBOE) and a holographic optical element (HOE). The PBOE is consisted of several regions of PB gratings with different periods and orientations. We have achieved 3*1 viewing points and a DOF of 4.4 Diopters.